The compliance time costs of Malaysian personal income tax system: E-filers vs. Manual-filers - Ibrahim, Idawati (Elsevier Ltd., 2014)
The main objective of this study is to estimate compliance costs for personal income tax (PIT) system in Malaysia and to investigate the effect of e-filing on compliance costs of PIT system in Malaysia.It is found that, on average, e-filing consumed about 10 hours while manual filing took about 13 hours. However, statistically, the difference is not significant.The findings suggest that e-filing is only a tool to facilitate the filing process.It is not meant to reduce the whole burden of annual filing for personal income taxpayers.